Role of Rehabilitation Center to Reduce Drug Abuse in Reference to Birendranagar Valley - Pathak, Dhanush Chandra; Saxena, Shalini (Nepal Journal of Multidisciplinary Research, 2019)
The substance that changes the physical, psychological and emotional function of individual is called drug. Any one may abuse drug to feel good, forget stress, and avoid reality. Drug abuse or substance abuse means using a drug for the purpose of creating pleasurable effects on the brain. A place where people of drug addiction are treated is called rehabilitation Centre. The core objective of this study is to find out the roles of rehabilitation center to reduce drug using habit of drug abusers who are undergoing for treatment in rehabilitation center. Mixed research method was used to analyze the data from 40 male respondents of Benevolence Rehabilitation Center, Surkhet. Birendranagar valley of Nepal. Purposive sampling technique was used to select the respondents. Frequency table was used to analyze the quantitative data. Roles and services of rehabilitation center had covered the different activities practices in rehabilitation center. It had covered the counseling, vocational training, meditation, realization programme, job opportunity, acceptance, programme, sympathy.